Medsebojno delovanje zdravil brez recepta z drugimi zdravili - Kerec Kos, Mojca (Farmacevtski vestnik, 2011)
For minor health problems prescription free medicines are often being used. In general these medicines are regarded as safe, almost without any side-effects and precautions for use. However, prescription free medicines canal so interact with other drugs and some drug interactions can have serious outcomes. In the article the most important drug-drug interactions for frequently used prescription free medicines are presented.
Keywords: interakcije; medsebojno delovanje; pantoprazol; ranitidin; zdravila brez recepta